Comparação entre duas técnicas de descongelamento de sêmen humano normozoospérmico de indivíduos férteis e inférteis: estudo duplo-cego prospectivo - Marco Aurelio Fernandes Vieira (2010)
The sperm quality of cryopreserved samples is still consideredunsatisfactory due to low recovery rate of viable sperm after freezing and thawing. In an attempt to improved quality of human cryopreserved semen, the present study was to compare two techniques of thawing in samples of normozoospermic men. Each semen sample after initial analysis of motility (light microscopy), concentration (counting in a Neubauer chamber), the strict morphology (Krugger criterion) and functional integrity of membranes (swelling test) was divided into 2aliquots of 0,5 ml each, which were frozen in cryopreservation medium TYB-G. A sample was thawed at room temperature for 25 minutes (thawed 1), and the other in a water bath at 75 ° C for 20 seconds followed by immersion in water bath at 37 ° C for 3 minutes (thawed 2). After thawing, the following parameters were evaluated and compared between the two samples: motility, strict morphology and functional integrity of membranes. The results were expressed as mean ± standard deviation for parametric variables and analyzed using t-student. Datawith non-parametric variables and unpaired were expressed as median(interquartile range) and analyzed by the Mann-Whitney. The level of significance was p <0,05. The total motility and progressive motility after thawing the fertile group with the technique of thawing 1 was 45,00 (10,00 - 50,00) and 40,00 (5,00 to 45,00), respectively. Using the technique of thawing 2 was 35,00 (20,00 to 60,00) and 30,00 (15,00 to 55,00), respectively. In the infertile group total sperm motility and progressive with the technique of thawing 1 was 40,00 (30,00 - 50,00) and 35,00 (25,00 45,00) respectively. With the use of the technique 2 was 45,00 (35,00 to 60,00) and 40,00 (25,00 - 55,00). Morphological forms in the normalfertile group with technique 1 was 18,00 and the technique 2 was 17,00. In the infertile group with technique 1 was 15,00 and the technique 2, also 15,00. The swelling test in the fertile group with technique 1 was 46,00 and the technique 2 was 41,81. In the infertile group with technique 1 was 47,00 and the technique 2 was 50,00. The results showed no statistically significant difference when comparing the evaluated parameters between the two groups and the use of both techniques.